Pediatric anesthesia, intensive care and pain : standardization in clinical practice - Astuto, Marinella (Anesthesia, Intensive Care and Pain in Neonates and Children, 2013)
This book provides a comprehensive overview of current standards of anesthesia and intensive care in neonates and children, with a view to promoting standardization in clinical practice. The first part of the book, devoted to issues in intensive care, opens by considering scoring systems for the assessment of sick children. The diagnosis, prevention, and management of ventilator-associated pneumonia are then discussed, and the roles of high-frequency oscillatory ventilation and noninvasive respiratory support are reviewed. Further chapters address procedural sedation and analgesia in children, the progress toward 'open' ICUs with liberal visiting policies, and advances in long-term home mechanical ventilation. In the second part of the book, a range of important topics in anesthesia and perioperative medicine are discussed. After a review of safety issues, current trends in pediatric regional and locoregional anesthesia are described and a synopsis is provided on current knowledge regarding the use of central blocks in infants and children. Subsequent chapters are devoted to awareness monitoring, single-lung ventilation techniques, anesthesia in the context of severe prematurity, and emergence delirium. Pediatric Anesthesia, Intensive Care and Pain: Standardization in Clinical Practice will be an extremely useful source of information for both novices and more experienced practitioners in the field.